ANALISIS PERAN INFLUENCER MARKETING DAN CONTENT MARKETING DALAM MENDORONG KEPUTUSAN KONSUMEN MENGINAP DI HOTEL BINTANG EMPAT - Widiastuti, Aprillia Anggun; Zusrony, Edwin; Andriana, Myra; Asti, Pindo (JURNAL LENTERA BISNIS, 2026)
This study aims to investigate the impact of influencer marketing and content marketing on consumer decisions to stay at the four-star Griya Persada Bandungan hotel, Semarang Regency, Central Java. This study uses a quantitative approach involving 60 respondents aged 20-40 years and selected using a purposive sampling technique. The data analysis technique uses multiple linear regression and is processed using SmartPLS version 4.1.1.2. The research findings prove that influencer marketing and content marketing have a positive and significant impact partially on consumer decisions to stay at the four-star Griya Persada hotel. Influencer marketing and content marketing have a simultaneous impact on consumer decisions to stay at the four-star Griya Persada hotel. These findings underscore the importance of influencer marketing and content marketing in increasing consumer decisions to stay at the four-star Griya Persada hotel.